DO THEY COME WITH THE BUILDINGS? “MODERNIZATION” AND PRECARIOUS WORK AT UNIVERSITY OF COSTA RICA (UCR) - Caamaño Morúa, Carmen (2022)
This article is the result of a first exploratory and descriptive inquiry about cleaning services outsourcing at the University of Costa Rica. It is based on documentary and social network content analyses, and on non-participant observation, to give account of the characteristics in which precarious labor is developed by one sector of the university community that has been made invisible. However, it lives in a space that still calls itself humanistic within the framework of the public university neoliberal “modernization”.